A Facility-Based Survey of Maternal Anti-Tetanus Vaccination Schedule Completion in a Nigerian University Community - JO Imaralu; AO Adekoya; AA Akadri; FE Bamidele; CC Nwankpa; JO Sotunsa (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2022)
Background: Maternal anti-tetanus vaccination is required to prevent maternal and neonatal tetanus. In the absence of lifetime protective dosing, repeat vaccination in every new pregnancy is needed to achieve protection of the newborn against tetanus. Objectives: To determine maternal anti-tetanus vaccination schedule completion rates and the reasons for non-completion of the schedule. Methods: This cross-sectional survey was conducted among Nigerian antenatal clinic attendees using an interviewee-administered questionnaire. Results: Most (291/347; 83.9%) respondents had received a TT vaccine in the index pregnancy, and 280/347 (80.7%) received their first TT injection at the booking visit. In comparison, 202/238 (84.9%) of those eligible had received tetanus toxoid protective immunisation (TTPDI) in the index pregnancy. Although a majority (301/347; 86.7%) of the respondents had received at least a dose of TT in a previous pregnancy, only 23/246 (9.3%) eligible pregnant women had received complete vaccination (TT5) Parity (p<0.001) and ethnicity (0.013) were the main determinants of the maternal tetanus vaccination schedule (TT5) completion. However, the socio-demographic characteristics were similar for TTPDI. The commonest reason for non-completion was forgetfulness 172/218 (78.9%), and most (287/347; 89.1%) of the respondents wished to receive telephone reminders. Conclusions: Although neonatal tetanus protective dosing of TT in the current pregnancy was high, a low proportion of mothers completed the five doses recommended by the WHO for lifetime immunity.